A proposed vision for the use of artificial intelligence in education by teachers of students with intellectual disabilities - Elsayed, Ahmed Ragab; Alfawzan, Sarah Khaled (International Journal of Innovative Research and Scientific Studies, 2025)
The study aimed to identify the attitudes of teachers of students with Intellectual Disabilities (ID) towards the use of Artificial Intelligence (AI) applications in education and its obstacles, with the presentation of a proposed vision for the use of these applications in education. The study sample consisted of teachers of students with ID in the primary stage in Al-Ahsa, numbering 179 male and female teachers. The study used a descriptive analytical approach, which was represented in the design of the study tool (questionnaire). The results of the study showed a low degree of negative attitudes among teachers of students with ID towards the use of AI in education with their students, and a high degree of obstacles to its use in education with these students. Based on the results, the researchers prepared and designed the proposed vision for the use of AI applications in education by teachers of students with ID.